2014
DOI: 10.1007/bf03356499
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intercropping with birdsfoot trefoil and summer savoury in reducing damage inflicted by onion thrips (Thrips tabaci, Thysanoptera, Thripidae) on four leek cultivars

Abstract: Onion thrips, Thrips tabaci (Thysanoptera, Thripidae), are an important pest of leek (Allium porrum) in Slovenia, and their control is becoming increasingly difficult for several reasons (e.g., increased resistance, specific life cycle). Therefore, intercropping, whereby the seeds of a different plant species are sown amidst the primary crop, represents a promising method to prevent pest damage. Our field experiments were conducted in 2009 and 2011, during which we studied the suitability of two different inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…In contrary, Mohammadhosseini and Beiranvand (2013) showed that the monoterpene hydrocarbons such as myrcene, α-pinene, β-pinene, α-terpinene, and α-thujene had the highest amount in the S. hortensis essential oil. These differences in the chemical profile of S. hortensis essential oil in the present and above-mentioned studies can be due to the variations in some of the influential factors, such as geographical and growing conditions, drying and extraction methods, ontogenetic stages, and season (Sefidkon et al, 2006;Pfefferkorn et al, 2008;Rezvanpanah et al, 2011;Ghorbanpour et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In contrary, Mohammadhosseini and Beiranvand (2013) showed that the monoterpene hydrocarbons such as myrcene, α-pinene, β-pinene, α-terpinene, and α-thujene had the highest amount in the S. hortensis essential oil. These differences in the chemical profile of S. hortensis essential oil in the present and above-mentioned studies can be due to the variations in some of the influential factors, such as geographical and growing conditions, drying and extraction methods, ontogenetic stages, and season (Sefidkon et al, 2006;Pfefferkorn et al, 2008;Rezvanpanah et al, 2011;Ghorbanpour et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…It used in Iranian traditional medicine to treat intestinal and stomach disorders such as indigestion and diarrhea, muscle pain, thrombosis, and cardiovascular diseases (Hajhashemi et al, 2000;Yazdanparast et al, 2008). Moreover, along with antibacterial, antifungal, antioxidant, and cytotoxic activities of S. hortensis, its potential on the insect pest management have also been documented (Mahboubi & Kazempour, 2011;Miladi et al, 2013;Gombač & Trdan, 2014;Farzaneh et al, 2015;Ghorbanpour et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thrips tabaci LIMDEMAN, 1889 is an onion pest that occurs in most areas of onion production globally and is of economic importance (LEWIS 1973). It has been recorded on plants from 29 families (RASPUDIĆ & IVEZIĆ 1999) and in Europe, Africa and in other continents is regarded as a pest of onion, leek and cabbage (DIAZ-MONTANO et al 2010, GOMBAČ & TRDAN 2014, LIU & SPARKS 2003, MANIANIA et al 2003, PÉNZES et al 1996, TRDAN 2003. T. tabaci causes significant economic losses in that it Can reduce yields by up to 60% (WAIGANJO et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…palmi , where the development of pupal stages usually takes place in the soil and this stage constitutes about 40% of the length of a full life cycle [ 5 , 6 ]. During this time, these insects are virtually inaccessible to the majority of chemicals and furthermore biological control is only partly effective for these pests [ 7 , 8 ]. Importantly, another problem in combating these serious pests is the difficulty in distinguishing non-quarantine F .…”
Section: Introductionmentioning
confidence: 99%